1996
DOI: 10.1111/j.1600-0447.1996.tb10635.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketoacidosis as a side‐effect of clozapine: a case report

Abstract: We report the case of a patient fulfilling DSM-IV criteria for schizophrenia and treated with clozapine who later developed hyperglycemia and ketoacidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…3 The chemical structure of clozapine (a) resembles that of olanzapine (b) apart from the fact that the clozapine structure is halogenated with a chlorine atom (a→) while olanzapine is not (b) and that the olanzapine molecule includes a thieno ring (b→) in place of the benzo ring of clozapine (a) (Budavari et al 1996) in glycemic control of already diagnosed diabetes after the beginning of clozapine or olanzapine therapies (Short and Nolan 1995;Kostakoglu et al 1996;Popli et al 1997;Ai et al 1998;Wirshing et al 1998;Goldstein et al 1999), two previous studies have pointed to an influence of clozapine on glucose-insulin homeostasis (Yazici et al 1998;Melkersson et al 1999), whereas in olanzapine-treated patients, no comparable studies of glucoseinsulin levels have been carried out. Previous studies have, however, reported elevated blood lipid levels during both clozapine and olanzapine treatments (Ghaeli and Dufresne 1996;Dursun et al 1999;Gaulin et al 1999;Osser et al 1999;Sheitman et al 1999;Spivak et al 1999), which supports the theory that both clozapine and olanzapine may influence glucose-insulin homeostasis by inducing insulin resistance, since hyperlipidemia may be connected with insulin resistance and secondary increased insulin secretion (Olefsky 1997).…”
Section: Discussionmentioning
confidence: 98%
“…3 The chemical structure of clozapine (a) resembles that of olanzapine (b) apart from the fact that the clozapine structure is halogenated with a chlorine atom (a→) while olanzapine is not (b) and that the olanzapine molecule includes a thieno ring (b→) in place of the benzo ring of clozapine (a) (Budavari et al 1996) in glycemic control of already diagnosed diabetes after the beginning of clozapine or olanzapine therapies (Short and Nolan 1995;Kostakoglu et al 1996;Popli et al 1997;Ai et al 1998;Wirshing et al 1998;Goldstein et al 1999), two previous studies have pointed to an influence of clozapine on glucose-insulin homeostasis (Yazici et al 1998;Melkersson et al 1999), whereas in olanzapine-treated patients, no comparable studies of glucoseinsulin levels have been carried out. Previous studies have, however, reported elevated blood lipid levels during both clozapine and olanzapine treatments (Ghaeli and Dufresne 1996;Dursun et al 1999;Gaulin et al 1999;Osser et al 1999;Sheitman et al 1999;Spivak et al 1999), which supports the theory that both clozapine and olanzapine may influence glucose-insulin homeostasis by inducing insulin resistance, since hyperlipidemia may be connected with insulin resistance and secondary increased insulin secretion (Olefsky 1997).…”
Section: Discussionmentioning
confidence: 98%
“…That is to say, the effect of clozapine on glucose metabolism developed in a very short period of 1±5 weeks. The dosage of clozapine at the point of impaired glucose tolerance was 50, 150, 250, 300 mg in each patient respectively, and 75 mg in two patients, this result suggests that a lower dosage than the 250±500 mg of the previous case reports (Kamran et al, 1994;Kostakoglu et al, 1996;Koval et al, 1994;Peterson and Byrd, 1996;Pierides, 1997;Popli et al, 1997;Wirshing et al, 1998) can develop impaired glucose tolerance. Considering that one study shows the optimal dosage of antipsychotics is lower in oriental people, including Koreans, than in western people (Young-Soon Kweon et al, 1996), the dosage inducing hyperglycemia as a side effect of clozapine may be variable according to the race, so future study in this area is needed.…”
Section: Discussionmentioning
confidence: 46%
“…In our clinical experience, it was impossible to ®nd a case that developed the severe problem of induced diabetes mellitus after chronic use of those antipsychotics. Concern about the effect of clozapine on blood glucose has developed recently by succeeding case reports that hyperglycemia or diabetic ketonuria developed after clozapine treatment (Kraman et al, 1994;Kostakoglu et al, 1996;Koval et al, 1994;Maxwell et al, 1990;Perterson and Byrd, 1996;Pierides, 1997;Popli et al, 1997;Wirshing et al, 1998) and especially in patients with a family history of diabetes mellitus (Kostakoglu et al, 1996;Koval et al, 1994;Perterson and Byrd, 1996;Popli et al, 1997) or the obese patient (Kostakoglu et al, 1996;Popli et al, 1997), there have been many reports of hyperglycemia developing after clozapine treatment. In the real clinical ®eld, unlike other antipsychotics, it is reported that clozapine induced diabetic ketoacidosis which caused the patient to become stuporous (Perterson and Byrd, 1996) and having a comatose mentality which required ventilatory support (Koval et al, 1994), therefore the possibility of being life threatening arose and the necessity of measuring the blood glucose level during clozapine treatment has been suggested.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that drugs may have a direct effect to decrease insulin secretion or cause insulin resistance directly, and that there are weight related effects of drugs on metabolic parameters including glucose and lipids. In light of the preceding, it is noteworthy that many case studies have reported at least a temporal association between impaired glucose tolerance and psychiatric medications including the phenothiazines (Thonnard-Neumann, 1968), HAL (Mukherjee et al, 1989), loxapine (Tollefson and Lesar, 1983), and QUET (Sobel, et al, 1999), RIS (Melamed et al, 1998;Croakin et al, 2000), CLZ (Lamberti et al, 1992;Koval et al, 1994;Kostakoglu et al, 1996;Popli et al, 1997;Mir and Taylor, 2001), and OLZ (Lamberti et al, 1992;Wirshing et al, 1998;Lindenmayer and Patel, 1999;Rigalleau et al, 2000;Mir and Taylor, 2001). Reports also suggest an association between antipsychotic medications and diabetes (Lamberti et al, 1992;Leadbetter et al, 1992) and cardiovascular disease (Koval et al, 1994;Popli et al, 1997).…”
Section: Glucose Dysregulationmentioning
confidence: 99%